A call to action for inventorying and monitoring of cliff ecosystems to support conservation - Harrison, Georgia R.; Boggess, Laura M.; McCord, Sarah E.; March-Salas, Martí (Basic and applied ecology, 2024)
•Cliffs are home to rare and endemic species but are under threat from increasing disturbance.•Monitoring can provide land managers with the site-specific information needed to support cliff conservation.•Monitoring methodologies should be standardized, easy to implement, and dependent on objective criteria.•We urge the development and proliferation of cliff monitoring projects, especially those which include community participation.•To facilitate success, specialists should lead a platform to integrate, process, and analyze information collected through monitoring. Cliffs harbor unique and specialized biodiversity that warrants attention and conservation. At the same time, cliffs are under increased threat from anthropogenic disturbance and climate change. Since cliffs are highly heterogeneous, spatially isolated, and often inaccessible compared to nearby habitats, land managers require up-to-date and site-specific information to protect them. Cliffs are often overlooked due to the technical and logistical challenges posed by surveying these environments, but field inventorying and monitoring can fill this gap. We present three case studies of cliff monitoring in action: mapping populations of an endemic rare plant in the Southern Appalachian Mountains (US), photo-sampling of cliff specialist plants in Spain, and surveying peregrine falcons in Western North Carolina (US). These case studies highlight the application of various monitoring techniques, the possibilities for collaboration among stakeholders, and some ways that data from monitoring can inform cliff conservation and stewardship. To facilitate the development of easy-to-implement monitoring, we outline three approaches and associated best practices for monitoring cliff plants. Methods range from simple photo point monitoring to more in-depth species inventories and could be implemented by community scientists alongside a broader audience interested in providing up-to-date data on cliff environments. We call for action, urging the expansion and advancement of cliff biodiversity monitoring.